Electronic Animal Identification Systems at Livestock Auction Markets: Adoption Rates, Costs, Opportunities, and Perceptions - Bolte, Kati; Dhuyvetter, Kevin C.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Buyers and sellers of livestock come together at livestock auction markets to discover prices in a public setting. Livestock markets may differentiate themselves by offering electronic individual animal identification and tracking services to their customers. Programs such as the National Animal Identification System (NAIS), marketing alliances, and verification programs are leading to an increased use of animal identification systems. Livestock markets are a primary industry sector where animal movement and identification information can be recorded. This project’s purpose was to determine livestock market manager perceptions about animal identification systems, estimate costs of adopting animal tracking systems in auction markets, and assess factors related to adoption of animal ID systems in auction markets. To accomplish these objectives, a national survey of livestock auction markets was conducted in the winter of 2006. Results from completed surveys, representing 189 livestock auction markets, are reported.
Keywords: National Animal Identification System; Livestock markets; RFID